PENGARUH SISTEM FULLDAY SCHOOL TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS VIII SMP AL-ISLAM 1 SURAKARTA TAHUN AJARAN 2025/2026 - Brillian Kusuma Annisa Fitri; Mu’in Abdullah (STKIP Pesisir Selatan, 2025)
This study aims to (1) determine the level of implementation of the full-day school system at SMP Al-Islam 1 Surakarta in the 2025/2026 academic year. (2) Determine the character level of class VIII students of SMP Al Islam 1 Surakarta in the 2025/2026 academic year. (3) Determine whether or not there is a significant influence between the full-day school system on the character formation of class VIII students of SMP Al-Islam 1 Surakarta in the 2025/2026 academic year. To achieve the above objectives, the researcher used a quantitative research type with a correlation approach to determine the relationship between variable X and variable Y. The data collection technique used a Likert scale questionnaire. Sampling used purposive sampling. The data analysis technique used descriptive statistics. Hypothesis testing used Pearson product moment and simple linear regression. The results of the study showed that: (1) The implementation of the full-day school system showed a percentage of 38.5% with the highest frequency being in the calculation formula 66.71 > X ≥ 56.581 in the sufficient predicate. (2) Student character shows a percentage of 36.5% with the highest frequency in the calculation formula 66.19 > X ≥ 56.604 in the good predicate. (3) There is an Effect of the Implementation of the Fullday School System on Student Character with a moderate correlation category with a value of 0.438 confirmed using simple linear regression with the results of the equation Y = 38.516 + 0.415X, which means H0 is rejected and H1 is accepted.